Calculating feed costs with alternative lysine diets for high-lean growth gilts - Friesen, K.G.; Boland, Michael A.; Schinckel, A.P.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Data from two experiments were used to determine the feed cost per I of lean gain for high-lean growth gilts fed various digestible lysine levels (.54 to 1.04%). The cost for producing 1 lb of lean increased as live weight increased from 75 to 160 lb (Exp 1) and from 160 to 300 lb (Exp 2). However, in Exp I, the cost per lb of lean gain was minimized for gilts fed 1.04 and .94% digestible lysine (1.25 and 1.15% total lysine, respectively) from 75 to 90 lb and from 90 to 160 lb, respectively. These data are similar to the data for maximum rates of lean gain for grower gilts (75 to 160 lb), indicating that maximum gain is the most cost-effective gain during the grower period. During the finishing period (160 to 300 lb), maximal lean gain was attained for gilts fed .94% digestible lysine. However, cost of attaining this rate of lean gain was also the most expensive. The least feed cost per lb of lean gain was achieved when gilts were fed .84 and .54% digestible lysine (1.0 and .65% total lysine, respectively) from 160 to 180 lb and from 180 to 300 lb, respectively. In conclusion, these data indicate that feeding for maximum lean gain during the growing period (75 to 160 lb) results in least cost production. However, during the finishing period, economics will dictate the level of digestible lysine fed rather than maximum rate of lean gain.
Keywords: Swine; Modeling; Requirements; Economics